Vocational Education Network Optimization Program Implementation Problems and Solutions - Šīna, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the paper is to analyze two-year results of the optimization programs of vocational school network and vocational education balancing solutions in the European Social Fund project " Improvement of national qualification system, vocational education contents and co-operation among the bodies involved in vocational education." The topic is of particular importance as the prestige of vocational education is low, the school network optimization yielded no results and vocational training does not deliver the qualities and eduation demanded by the job market. Innovation of the article - there have not been evaluation of network optimization results. Methodology applied: monographic, study of related documents, survey,interviews. The author concludes that there is a lack of a differentiated vocational education network,which is appropriate to the demographic trends; and the funds have not been allocated properly. It is offered to create integrated schools, which would be implementing basic education, vocational programs, adult education and lifelong learning.